2005
DOI: 10.1002/chin.200518269
|View full text |Cite
|
Sign up to set email alerts
|

Substituted BEDT‐TTF Derivatives: Synthesis, Chirality, Properties and Potential Applications

Abstract: Abstract.The increasing availability of functionalized BEDT-TTF derivatives in both racemic and enantiopure forms opens up great opportunities for preparing multifunctional materials and chiral conducting systems in the form of crystals, thin films and polymers. Functionalities such as amino and carboxyl will allow attachment to other molecular systems, while intermolecular interactions between substituents, e.g. hydrogen bonding and halegon---halegon interactions, provides additional tools for designing solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…17 The possible influence of the structural disorder in the conducting properties of chiral TTF-based conductors has been initially addressed by Dunitz and Wallis through the synthesis of the first chiral TTF derivative, namely S,S,S,S-tetramethyl-BEDT-TTF (BEDT 5 bis(ethylenedithio). 18 Subsequently, many other chiral BEDT-TTF derivatives, with the chiral information provided by asymmetric carbon atoms in the backbone of the TTF-tetrathio unit, have been reported, especially by Wallis et al 19,20 Interestingly, amphiphilic TTF derivatives containing chiral long alkyl chains have also been described. 21 Polymerization of such a compound, bearing an isocyanide group, afforded a polymer in which chiral teleinduction was evidenced.…”
Section: Introductionmentioning
confidence: 98%
“…17 The possible influence of the structural disorder in the conducting properties of chiral TTF-based conductors has been initially addressed by Dunitz and Wallis through the synthesis of the first chiral TTF derivative, namely S,S,S,S-tetramethyl-BEDT-TTF (BEDT 5 bis(ethylenedithio). 18 Subsequently, many other chiral BEDT-TTF derivatives, with the chiral information provided by asymmetric carbon atoms in the backbone of the TTF-tetrathio unit, have been reported, especially by Wallis et al 19,20 Interestingly, amphiphilic TTF derivatives containing chiral long alkyl chains have also been described. 21 Polymerization of such a compound, bearing an isocyanide group, afforded a polymer in which chiral teleinduction was evidenced.…”
Section: Introductionmentioning
confidence: 98%
“…4 The access to a large library of chiral precursors is thus of paramount importance, and, accordingly, several families of TTFs, in which the chiral information has been addressed in different ways, have been described. 1 For example, derivatives with stereogenic carbon atoms such as bis(ethylenedithio)-tetrathiafulvalenes (BEDT-TTF), 5,6 TTF-oxazolines [7][8][9][10][11][12] and bis(oxazolines), 13,14 bis(pyrrolo)-TTFs, 15 C 3 symmetric tris(TTF) affording supramolecular helical aggregates, 16,17 or with stereogenic sulfur atoms in TTF-sulfoxides 18,19 have been reported. Complete series of conducting salts, comprising both enantiomeric and racemic forms, have been prepared by electrocrystallization of EDT-TTF-oxazolines (EDT = ethylenedithio).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the works of Flakina et al [ 8 ], revealed new molecules from the monosubstituted anion of isocyanuric acid on BEDT-TTF and their crystal structures were determined. The chirality of substituted BEDT-TTF derivatives was in the heart of work of Wallis et al [ 9 ]. In addition, gives opportunities for preparing multifunctional materials.…”
Section: Introductionmentioning
confidence: 99%